The Effect of Bariatric Surgery on Patients with Chronic Disease in KSMC - Aloraini, Abdullah Ahmed; Alsughayyir, Abdulelah Sulaiman; Alamri, Abdullah Khaled; Alshayea, Haitham Shayea; AlMesned, Mohammed (International Journal of Innovative Research in Medical Science, 2021)
Background: Obesity is a fast-growing global epidemic; it is associated with several comorbidities, including diabetes mellitus, hypertension, and dyslipidemia. Bariatric surgery is increasingly used due to its positive impacts on most of the comorbidities such as type 2 diabetes mellitus in patients with morbid obesity as it improves glycemia, lipids,blood pressure, andinflammation. Aim: To assess the effect of bariatric surgery on diabetic and dyslipidemic patients. Method: This is a retrospective study conducted on diabetic and dyslipidemic patients who underwent bariatric surgery. The study included the data of patients from 2009 to 2018 from KSMC. SPSS was used to analyze the collected data. Results: There were 808 diabetic patients included with a mean ±SD age of 42.1±11.05 years old, and 25 dyslipidemic patients with a mean ±SD age of 45.4±8.2 years. There were 72.4% of diabetic patients and 52% of dyslipidemic patients completed the treatment. Regarding diabetic patients, the outcome of patients was significantly associated with nationality (P˂0.0001) and the mean age of patients (P˂0.0001). The mean age had a significant impact on the outcome of the diabetic patients (P=˂0.0001) and had no effect in the case of the dyslipidemic patients (P=0.37). Conclusion: Bariatric surgery has a significant impact on chronic diseases such as diabetes and dyslipidemia, with a higher impact on diabetes compared to dyslipidemia.